Reporting of RT-PCR cycle threshold (Ct) values during the first wave of COVID-19 in Qatar improved result interpretation in clinical and public health settings. Issue 5 (16th May 2022) - Coyle, Peter V.; Al Molawi, Naema Hassan; Kacem, Mohamed Ali Ben Hadj; El Kahlout, Reham Awni; Al Kuwari, Einas; Al Khal, Abdullatif; Gillani, Imtiaz; Jeremijenko, Andrew; Saeb, Hatoun; Al Thani, Mohammad; Bertollini, Roberto; Abdul Rahim, Hanan F.; et al.
Abstract : Introduction. The cycle threshold (Ct) value in real-time PCR (RT-PCR) is where a target-specific amplification signal becomes detectable and can infer viral load, risk of transmission and recovery. Use of Ct values in routine practice is uncommon. Gap Statement. There is a lack of routine use of Ct values when reporting RT-PCR results in routine practice. Aim. To automatically insert Ct values and interpretive comments when reporting SARS-CoV-2 RT-PCR to improve patient management. Methodology. Routine Ct values across three different RT-PCR platforms were reviewed for concordance at presentation and clearance in patients with COVID-19. An indicative threshold (IT) linked to viral clearance kinetics was defined at Ct30 to categorize Ct values as low and high, reflecting high and low viral loads respectively. Results. The different gene targets of each platform showed high correlation and kappa score agreement ( P <0.001). Average Ct values were automatically generated with values ≤Ct30 reported as positive and >Ct30 as reactive; interpretive comments were added to all reports. The new reporting algorithm impacted on: physician interpretation of SARS-CoV-2 results; patient management and transfer; staff surveillance; length of stay in quarantine; and redefinition of patient recovery. Conclusion. Incorporation of Ct values into routine practice is possible across different RT-PCR platforms and adds useful information for patient management. The use of an IT with interpretive comments improves clinical interpretation and could be a model for reporting other respiratory infections. Withholding Ct values wastes useful clinical data and should be reviewed by the profession, accreditation bodies and regulators.